Combining backcasting with forest sector projection models to provide paths into the future bio-economy. Issue 7 (2nd October 2016) - Sjølie, Hanne K.; Latta, Greg S.; Solberg, Birger
ABSTRACT: Backcasting is a widely used method that first envisions future desirable goals and thereafter identifies the necessary steps to reach that state. A recent report released by a large group of key stakeholders sets ambitious goals for the Norwegian forest sector in the decades to come, and recommends a set of actions for reaching these goals. As in many backcasting studies, the report provides no assessment of the effects of the identified actions. The objective of our study was to use a model that covers the main product flows in the Norwegian forest sector to evaluate the effectiveness of various recommendations in the report toward meeting the goal of increasing the national annual harvest level from the current level of about 11 million m 3 to 15 million m 3 in 2045. We simulated a set of scenarios across the sector, and found that to reach the harvest level goal, multiple and radical actions would be required. Interlinkages between segments are important features that impact the results. Simulating recommendations in a model that covers the main product flows and attributes in the sector aids in understanding where policies may have the greatest impact and thus may increase the policy relevance of backcasting.